MENCARI KEBENARAN DI DALAM SAINS Kajian atas Gagasan Ian G. Barbour dalam Buku Issues in Science and Religion - Islah Gusmian (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2014)
Abstract: This article tries to describe the main idea ofBarbour‟s work on Issues in Science and Religion related to scientificmethods. According to Barbour, three criteria are used to evaluate atheory: it should match with observations, the internal relationshipbetween the theories and concepts, and its comprehension. Barbouroutlines some views in relation to the theory of science tradition. Thereare four views, all of which have differences to apply the theory in thestudy of science, namely positivism, instrumentalism, Idealism, andRealism. Models of scientific discovery do not only give blessing forhuman life, but also a challenge for religious philosophical outlook.Scientific thoughts will be also able to open the forms of truth that liesin the sphere of personal life and human relationships